The Role of Pattern Recognition Receptor (PRR) in the Body's Defense System: A Narrative Literature Review - Ziske Maritska; Hidayat, Rachmat (Open Access Indonesian Journal of Medical Reviews, 2023)
Each cell has receptors on the cell surface that specifically bind to solutes (ligands) produced during tissue damage or infection. This review aimed to describe the role of PRR in the human body's defense system. The binding of the ligand to its receptor results in the activation of intracellular signaling pathways and cell activation. The B and T lymphocytes of the adaptive immune system have developed surface receptors (that is, the T-cell receptor, or TCR, and the B-cell receptor, or BCR) that bind a broad spectrum of antigens. The cells involved in innate resistance have developed a distinct set of receptors that recognize a much more limited array of specific molecules. These are called pattern recognition receptor (PRR), and they recognize the molecular patterns in infectious agents or their products (pathogen-associated molecular patterns, or PAMP) or products of cellular damage (necrosis or apoptosis; molecular pattern-associated damage, or DAMPs). In conclusion, the pattern recognition receptor (PRR) is a receptor complex that interacts with various molecules, such as PAMP and DAMPs. PRR bonds with these various molecules and play a role in various actions of innate immunity and adaptive immunity.